Exploring an Unknown Corner of a Well-Known Topic: HIIE Influence on Renal Health and Filtration in Healthy Individuals Free of Cardiometabolic Diseases - Jeffrey S. Forsse; Kathleen A. Richardson; Ricardo Torres; Catherine Lowry; James Kyle Taylor; Cassidy L. Beeson; Jacob Ward; Anurag Dhillon; Brock Niceler; Ahmed Ismaeel; Panagiotis Koutakis (MDPI AG, 2023)
Aerobic exercise, specifically high-intensity interval exercise (HIIE), and its effects on renal health and filtration (RHF) are not well understood. Several studies support incorporating contemporary biomarkers serum cystatin C (CyC) and urine epidermal growth factor (uEGF) to combat the volatility of serum creatinine (sCr). Using these biomarkers, we examined the acute influences HIIE has on RHF to determine if there is a ceiling effect in healthy populations. The purpose was to determine the influence of an acute bout of HIIE on RHF. Thirty-six participants (n = 22 males; n = 14 females; age 37.6 ± 12.4 years.; BF% 19.2 ± 7.1%; VO2max 41.8 + 7.4 mL/kg/min) completed 30 min of HIIE on a treadmill (80% and 40% of VO2reserve in 3:2 min ratio). Blood and urine samples were obtained under standardized conditions before, 1 h, and 24 h post-exercise. CyC, sCR, uEGF, urine creatinine (uCr), uCr/uEGF ratio, and multiple estimates of glomerular filtration rate (eGFR) Modification of Diet in Renal Disease (MDRD) and CKD-EPI equations were used. The analysis employed paired sample t-tests and repeated measures ANOVAs. CyC, uEGF, uCr, and uCr/uEGF ratio concentrations were not altered between timepoints. sCr increased 1 h post-exercise (p > 0.002) but not at 24 h post-exercise. eGFR decreased in the MDRD and CKD-EPI equations at 1 h (p > 0.012) with no changes at 24 h post-exercise. CyC and sCr/CyC demonstrated no significant changes. CyC and uEGF are not altered by acute HIIE. The results demonstrate a potential ceiling effect in contemporary and traditional biomarkers of RHF, indicating improvements in RHF may be isolated to populations with reduced kidney function.